Development of phase shift lithography for the production of metal‐oxide‐metal diodes. (1st July 2014) - Dodd, Linzi E.; Rosamond, Mark C.; Gallant, Andrew J.; Wood, David
Abstract : Metal‐oxide‐metal (MOM) diodes have been produced by combining two novel techniques: a reactive ion etche and subsequent plasma oxidation, and a phase shift lithography process. This has resulted in a significant reduction in device feature sizes, down to sub‐micron dimensions and with an improved zero voltage curvature coefficient of up to 2.8 V −1 for the associated diodes. Given the use of MOM diodes in high speed rectification applications, the combination of the reduction in diode area as well as the controlled oxide growth aims to assist in the improved cutoff frequency of the devices, thus ensuring the potential for high speed applications.